2019
DOI: 10.1016/j.jneumeth.2018.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Minimalistic in vitro systems for investigating tau pathology

Abstract:  Misfolded tau spreads from cell to cell, and propagates in a prion-like manner.  In vitro and in vivo models exist that recapitulate aspects of tau pathology.  Microfluidic devices can recreate minimalistic, manipulatable neuronal arrays in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 122 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Tau pathology is propagated via synaptic activity (Wu et al., 2016), possibly through exosomes (Wang et al., 2017), as well as non‐synaptic mechanisms (Calafate et al., 2015). Studies using MPS have contributed to elucidate the prion‐like propagation of Tau, and to clarify tau species involved and effects on recipient cells (reviewed in (Hallinan, Pitera, et al., 2019)) and have more recently been used to screen Tau targeted prospective therapeutics. Using a three chamber MPS Nobuhara et al showed that some Tau antibodies, targeting the protein mid‐domain, efficiently blocked the Tau uptake, aggregation, and spreading (Nobuhara et al., 2017).…”
Section: Microfluidic Models Of Neurological Diseasesmentioning
confidence: 99%
“…Tau pathology is propagated via synaptic activity (Wu et al., 2016), possibly through exosomes (Wang et al., 2017), as well as non‐synaptic mechanisms (Calafate et al., 2015). Studies using MPS have contributed to elucidate the prion‐like propagation of Tau, and to clarify tau species involved and effects on recipient cells (reviewed in (Hallinan, Pitera, et al., 2019)) and have more recently been used to screen Tau targeted prospective therapeutics. Using a three chamber MPS Nobuhara et al showed that some Tau antibodies, targeting the protein mid‐domain, efficiently blocked the Tau uptake, aggregation, and spreading (Nobuhara et al., 2017).…”
Section: Microfluidic Models Of Neurological Diseasesmentioning
confidence: 99%
“…Animal can be a common source of brain cells for in vitro cultures. These cells are usually extracted from different anatomical regions of the CNS and PNS of embryos, pups or adult rodents before being seeded into compartments of microfluidic devices (Kunze et al, 2011;Seibenhener and Wooten, 2012;Southam et al, 2013;Robertson et al, 2014;Ruiz et al, 2014;Hallinan et al, 2019). Despite the advantages of using animals, this approach has some limitations.…”
Section: Cell Culture Interactions In Microfluidic Devicesmentioning
confidence: 99%